Value of staging squamous cell carcinoma of the anal margin and canal using the sentinel lymph node procedure: an update of the series and a review of the literature - Mistrangelo, D M (Nature Publishing Group, 2013)
BACKGROUND: Inguinal metastases in patients affected by anal cancer are an independent prognostic factor for local failure and overall mortality. Since 2001, sentinel lymph node biopsy was applied in these patients. This original study reports an update of personal and previous published series, which were compared with Literature to value the incidence of inguinal metastases T-stage related and the overall incidence of false negative inguinal metastases at sentinel node. METHODS: In all, 63 patients diagnosed with anal cancer submitted to inguinal sentinel node. Furthermore a research in the Pub Med database was performed to find papers regarding this technique. RESULTS: In our series, detection rate was 98.4%. Inguinal metastases were evidentiated in 13 patients (20.6%). Our median follow-up was 35 months. In our series, no false negative nodes were observed. CONCLUSION: Sentinel node technique in the detection of inguinal metastases in patients affected by anal cancer should be considered as a standard of care. It is indicated for all T stages in order to select patients to be submitted to inguinal radiotherapy, avoiding related morbidity in negative ones. An overall 3.7% rate of false negative must be considered acceptable.